Laboratory substantiation of the efficiency of nanocomposite material prepolymerization heating - Z. S. Khabadze (Эндодонтия Today)
Aim. To evaluate the effectiveness of prepolymerization heating of composite filling materials.Materials and methods. For the study, two composite filling materials Enamel plus HRi® dentin and enamel were used. During the tests, the coefficient of linear thermal expansion, glass transition temperature, Young's modulus and penetration depth, electron scanning microscopy were determined.Results. According to the results of the study, the difference between heated and unheated dentin samples in terms of Young's modulus, as well as changes in the penetration depth in the samples of the original enamel and enamel after heating, was revealed.Conclusions. In the course of the work, it was found that the material that underwent preliminary heat treatment is much less deformed under load than the material that does not have a thermal history.